2014
DOI: 10.3109/02699206.2013.875593
|View full text |Cite
|
Sign up to set email alerts
|

Voice onset time and speakers’ age: Data from Hungarian

Abstract: The aim of this paper was to investigate the VOT of voiceless plosives (/p, t, k/) in the speech of Hungarian-speaking elderly. Read speech of 25 old (70 to 90 years) and 25 young (21 to 32 years) was analyzed. In each recording, the VOT of phonologically short [p, t, k] was measured. Our data show that VOT values of all three types of voiceless plosives would exhibit significant differences both in old and in young Hungarians' speech. Bilabial and alveolar plosives had significantly longer VOT in old subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
(34 reference statements)
2
7
1
2
Order By: Relevance
“…the same VOT category as was presented by Czech speakers. In general, our findings are quite well in agreement with these studies [17,18] as a group of Hungarian speakers composed predominantly of women demonstrated significantly shorter VOT of /p/ and /t/ in older (mean age 76.9 years) compared to younger group (mean age 25.3 years) [18] and a group of 130 male and 135 female Dutch-speaking participants demonstrated no significant change in duration of VOT of /p/ and /k/ [17].…”
Section: Fig 1: Results Of Correlation Analysis Between Speech Variasupporting
confidence: 93%
See 3 more Smart Citations
“…the same VOT category as was presented by Czech speakers. In general, our findings are quite well in agreement with these studies [17,18] as a group of Hungarian speakers composed predominantly of women demonstrated significantly shorter VOT of /p/ and /t/ in older (mean age 76.9 years) compared to younger group (mean age 25.3 years) [18] and a group of 130 male and 135 female Dutch-speaking participants demonstrated no significant change in duration of VOT of /p/ and /k/ [17].…”
Section: Fig 1: Results Of Correlation Analysis Between Speech Variasupporting
confidence: 93%
“…Interestingly, the shortening of consonant duration in women was preserved even when using VOT ratio thus cannot be interpreted as a simple effect of faster speaking rate. Our results can be compared to two previous studies investigating voiceless plosives in Dutch [17] and Hungarian [18] speaking subjects as they reported their speakers to produce short voicing lag, i.e. the same VOT category as was presented by Czech speakers.…”
Section: Fig 1: Results Of Correlation Analysis Between Speech Variasupporting
confidence: 53%
See 2 more Smart Citations
“…폐쇄음은 입술, 혀, 턱, 후두 사이의 세밀한 협응을 통해서 산출되기 때문에, 음성 제어 능 력을 폐쇄음으로 VOT를 측정할 수 있다고 알려져 있다 (Auzou et al, 2000). Koenig(2000) 폐쇄음의 조음위치는 VOT값에 영향을 미치는 것으로 보고 되며, 선행 연구 (Bona & Auszmann, 2014;Cho et al, 2002;Lundeborg et al, 2012;Han, 2013 (Broersma, 2010;Rami et al, 1999;Shin, 2010). Rami 외 (Kent, 1976;Kummer, 2014).…”
Section: 서론 성대진동개시시간(Voice Onset Time; Vot 이하 Vot)은 폐 쇄음 파열 이후부터 모음이unclassified